2007
DOI: 10.1016/j.febslet.2007.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Loss of putative tumor suppressor EI24/PIG8 confers resistance to etoposide

Abstract: Expression of p53-target gene EI24/PIG8 is lost in invasive breast cancers, suggesting that EI24/PIG8 is a tumor suppressor that prevents tumor spreading, and partially mediates p53-attributed tumor suppressor activity. EI24/PIG8 also has pro-apoptotic activity indicating that loss of EI24/PIG8 may modulate sensitivity to chemotherapy. Here it is demonstrated that suppression of EI24/PIG8 in fibroblasts and breast cancer cells significantly inhibits the apoptotic response to etoposide treatment. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…LTBR, a proapoptotic gene, was down-regulated in busulfan-resistant human myeloid leukemia cells compared to sensitive cells [50]. EI24, a p53-target gene, was lost in invasive breast cancers, and knockdown of EI24 conferred resistance to etoposide treatment in breast cancer cells [51]. SMAD2 expression is lower in glioma cells than in normal astrocytes [52].…”
Section: Discussionmentioning
confidence: 98%
“…LTBR, a proapoptotic gene, was down-regulated in busulfan-resistant human myeloid leukemia cells compared to sensitive cells [50]. EI24, a p53-target gene, was lost in invasive breast cancers, and knockdown of EI24 conferred resistance to etoposide treatment in breast cancer cells [51]. SMAD2 expression is lower in glioma cells than in normal astrocytes [52].…”
Section: Discussionmentioning
confidence: 98%
“…42 Increase in expression of EI24 by etoposide treatment has been reported in in vitro systems. 22,43 However, suppression of EI24 mRNA level inhibits etoposide-induced apoptosis. 43 Unlike us, Zhang et al 7 showed no significant difference in expression of LOH11CR2A in normal cervix and CACX by semiquantitative RT-PCR.…”
Section: Reduction In Mrna Expression Of the Candidate Tsgsmentioning
confidence: 99%
“…22,43 However, suppression of EI24 mRNA level inhibits etoposide-induced apoptosis. 43 Unlike us, Zhang et al 7 showed no significant difference in expression of LOH11CR2A in normal cervix and CACX by semiquantitative RT-PCR. Low expression of LOH11CR2A transcripts by Northern blot analysis was found in breast, ovarian and lung cancer cell lines.…”
Section: Reduction In Mrna Expression Of the Candidate Tsgsmentioning
confidence: 99%
“…Overexpression of Ei24 suppresses cell growth and induces apoptosis, while depletion of Ei24 results in suppression of apoptosis in response to pro-apoptotic treatment (2)(3)(4). The human EI24 gene is located on chromosome 11q23, a region frequently displaying loss of heterozygosity in several malignancies, including invasive cervical cancers, breast carcinomas and malignant melanoma (5).…”
mentioning
confidence: 99%